Exploring the impact of marketing culture on job satisfaction Evidence from the Turkish banking sector - Yildirim, Seda; Acaray, Ali; Aydin, Kenan (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - The literature has shown that organizational culture influences job satisfaction in various industries such as tourism, banking and retail. As a result, investigating the impact of culture and organizational structure is a topic of growing interest. In this context, the purpose of this paper is to examine whether marketing culture has a positive effect on job satisfaction in banking firms. Design/methodology/approach - This study employed a survey methodology. Surveys were conducted in Istanbul, Turkey, with service industry employees of private banks and insurance companies. To measure the marketing culture, Webster's (1990) marketing culture model with 34 items was adopted. Six basic dimensions of service quality, interpersonal relationships, selling task, organization, internal communication and innovativeness were measured using the survey instrument. Job satisfaction was measured using the 20-item Minnesota Satisfaction Questionnaire on the following two dimensions: intrinsic satisfaction and extrinsic satisfaction. The data were analyzed with SmartPLS 2.0 and SPSS 21 programs. Findings - It was found that marketing culture had a significant and positive effect on job satisfaction. In particular, the marketing culture factors had a greater effect on extrinsic satisfaction in banking firms. In this regard, service quality, organization, selling task and innovativeness had a positive effect on extrinsic satisfaction. Originality/value - This study supports the argument that the concept of marketing culture is different from the market-oriented culture type. In addition, this study shows that marketing culture has a positive effect on job satisfaction in banking firms.
Keywords: Job satisfaction; Organizational culture; Banking sector; Marketing culture; ORIENTED ORGANIZATIONAL CULTURE; PERFORMANCE; COMMITMENT; TURNOVER; MODEL; Business & Economics